The organization of the pyramid texts : typology and disposition - Hays, Harold M. (Probleme der Ägyptologie, 2012)
The ancient Egyptian Pyramid Texts form the oldest body of religious texts in the world. This book weds traditional philology to linguistic anthropology to associate them with two spheres of ritual action, mortuary cult and personal preparation for the afterlife.